Surfactant Modified/Mediated Thin-Layer Chromatographic Systems for the Analysis of Amino Acids - Showkat A. Bhawani; Hassan M. Albishri; Ziya Ahmad Khan; Mohamad N. Mohamad Ibrahim; A. Mohammad (Journal of Analytical Methods in Chemistry)
This review incorporates a large number of chromatographic systems modified by the surfactants. A large number of solvent systems and stationary phases are summarized in this paper. Three different kinds of surfactants (anionic, cationic, and nonionic) are used as modifiers for stationary phases as well as solvent systems. Surfactants are used at all the three different concentration levels (below, above, and at critical micelle concentration) where surfactants behave differently. Modifications of both stationary phases and solvent systems by surfactants produced a new generation of chromatographic systems. Microemulsion solvent systems are also incorporated in this paper. Microemulsion thin-layer chromatography is a new approach in the field of chromatography.